การรับรู้เกี่ยวกับยาปฏิชีวนะและการร้องขอยาปฏิชีวนะของชนเผ่า ในตำบลปางหินฝน อำเภอแม่แจ่ม จังหวัดเชียงใหม่ - เกษมชัย บุญเป็ง (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
This descriptive study included a cross-sectional analytical study aiming to assess the incidence of requesting antibiotics, and related factors among hill-tribal patients receiving services from a Sub-district health promoting hospital. The study also included a qualitative study by conducting a semi-structured interviewto understand the perception about antibiotics of three tribes-Hmong, Karen, and Lua-in Panghinfon sub-district, Mae Chaem district, Chiang Mai province, between April and May 2015. The study found that among 200 samples, average age of 38.5 years (20-64), most of them were eligible for the universal health coverage scheme (88.5 %), and ratios of the three tribes were in related amount. Most of them received services on respiratory diseases, muscular and skeletal system, and endocrine system. The incidence of requesting antibiotics found was more than one-third of the patients receiving services (36.5 %) and 61.6 % of thoserequesting antibiotics were prescribed. Most of them requested antibiotics for themselves (67.1 %). The only factor significantly associated with the request of antibioticswas the ICD10disease classification (p <0.001). Patients with respiratory disease (83.9 %) and skin diseases (71.4 %) requested antibiotics more than any other disease groups. It was found that gender, health insurance scheme, tribe,and age were not the factors associated with a request of antibiotics. Instead, the factors significantly associated with a request of antibiotics were disease group (skin disease), antibiotics request, and a request for self-medication (p <.001, p <.001, p = .010, respectively). The results of the interview showed that the perception and behavior of seeking antibiotics among the three tribes were not much different. The request of antibiotics or “ya-kae-ak-sep” and “ya-lod”, called differently among tribes, was a phenomenon seen in health settings resulting from many related factors. According to the Health Belief Model, when hill tribal patients in Panghinfon sub-district were ill, they would perform a primary care. However, due to their recognition of the importance of health to the ability to work, care for agricultural crops, income to the family, as well as not to be a burden to family members who may have to stop working in order to take care of them, if patients did not feel better from the symptom by self-care,they considered taking drugs. The tribal groups recognized and defined "inflammation (ak-sep)" as pain, swelling, and pus on the body, and "antibiotics (ya-kae-ak-sep)" as a potent drug which helps them to recover from the inflammation faster than conventional medicine. Such recognition resulted from experiences of using antibiotics, information from neighbors and medical personnel, and the media claiming that antibiotics could treat inflammation. Moreover, antibiotics could be easily accessed from the sharing of relatives or neighbors, grocery stores located nearby or accessible clinics, and familiar hospital staff. Thus, this resulted in seeking behavior of antibiotics. Although some tribes had received information from health officials about the importance of taking a full course of antibiotic treatment, and most of them recognized that the drug caused drug allergies (rash, swelling, and suffocation) or even death, as well as the perception of drug resistance the drug taken formerly could not cure the disease this awareness was not only specific to antibiotics. The patients often stopped taking medication when the symptoms subsided and they had never faced the problem of antibiotic use in person. As a result, when it was necessary to recover from illness, they seek treatment by requesting antibiotics. Therefore, promoting rational use of antibiotics in the area needs to be carried out at various levels and among partnership networks by enhancing the knowledge and awareness of the dangers of antibiotics, communication and negotiation skills of public health staff who are requested antibiotics by patients, and supporting health media to sufficiently educate people in the area, as well as organizing the environment at community level in order to access antibiotics safely when patients seek treatment. Further studies should consider expanding the area where people request antibiotics to cover grocery stores, private clinics, and hospitals. There should also be a more in-depth study among other stakeholders in order to promote a rational and sustainable use of antibiotics in common areas.